ANALISIS PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI ALFAMART SONGGOM - Winda Sofiana Sundari; Bambang Riono, Slamet; Dwi Harini (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
The decision to purchase household products of residents of Songgom, Songgom District, Brebes Regency decreased. The number of components that consumers consider in choosing an item is due to business developments in the trade sector. This makes buyers more specific in determining purchase decisions, for example at PT Sumber Alfaria Trijaya (Alfamart). This research was conducted in Alfamart, Songgom District, Brebes Regency. The existence of business competition makes Alfamart Songgom need to improve promotional procedures in increasing the number of buyers. The aim of this research is to determine the influence of promotion and service quality on purchasing decisions at Alfamart Songgom. The data used is primary data by distributing questionnaires to consumers at Alfamart Songgom. The population in this study were visitors or buyers at Alfamart Songgom. The number of samples in this test was 145 respondents who were determined using the Slovin formula. The data analysis procedures used are instrument tests, classical assumption tests, multiple regression tests. The results of the t test obtained a promotion variable sig value of 0.001 < a α value (0.05), a service quality variable of 0.010 < a α value (0.05, so it was declared to have a partial effect. The results of the F test obtained a sig value. of 0.000 < 0.05, explaining that promotion and service quality have a significant influence on purchasing decisions at Alfamart Songgom.